Pengaruh Penambahan Komposisi Hidroksiapatit Terhadap Pengurangan Massa Membran Jaringan Terpadu Untuk Aplikasi Biomaterial - Geo Rayfandy; Jhon Armedi Pinem; Irdoni HS (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Guided Tissue Regeneration (GTR) is one of the techniques used in periodontitis patients to treat tooth decay which provides an opportunity for the growth of new teeth. The purpose of this study is the synthesis of GTR membrans from chitosan, hydroxyapatite, and PEG and study the effect of variations in the composition of hydroxyapatite respectively 2, 4, and 6 gr. The membran is made from a mixture of chitosan, PEG and hydroxyapatite solution which is stirred until homogeneous. The results of the mixture are printed with a glass plate and characterized by membran biodegradation. The effect of adding hydroxyapatite composition to the GTR membran is increasing membran biodegradation. Keywords: chitosan, GTR, hydroxyapatite, membran, PEG.